Observed Steep and Shallow Spectra, Narrow and Broadband Spectra, Multifrequency Simultaneous Spectra, and Statistical Fringe Spectra in Fast Radio Bursts: Various Faces of Intrinsic Quasi-periodic Spectra? - Shu-Qing Zhong; Wen-Jin Xie; Jia-Hong Gu (The Astrophysical Journal)
Through analysis, modelings, and simulations, we show that if the spectra of fast radio bursts (FRBs) are intrinsically quasi-periodic, and likely produced by coherent curvature radiation from quasi-periodic structured bunches, then the observed steep and shallow spectra, narrow and broadband spectra, multifrequency simultaneous spectra, as well as possible statistical fringe spectra in FRBs, could all be various manifestations of them. If so, the period properties of the structured bunches, as inferred from the observed multifrequency simultaneous spectra and potential statistical fringe spectra, may provide valuable insights into the mechanisms behind the formation of such structured bunches.